Fans' self-identity crisis and reconstruction in the context of idol disgraced: Evidence for a self-identity configuration - Wenbo Huang; Jianquan Zhou; Xuanhong Yi; Xingwei Jing (Acta Psychologica)
With the advancement of information technology and the widespread popularity of fan culture, fan communities have developed a set of complex, self-serving identity processes configuration. This research explores the crisis and reconstruction of fan self-identity in the context of idol disrepute from a social psychological perspective. To provide a deeper analysis, the study employs grounded theory and gathers data through semi-structured interviews with fans of disreputed idols. The findings reveal that, when confronted with idol disrepute, fans typically experience a complex psychological process, progressing from confusion and denial to reevaluation and reconstruction of their self-identity. Throughout this process, fans often cope with the shock of idol disrepute by severing their identity ties with the idol, engaging in mutual support, and reflecting personally. Importantly, idol disrepute does not always result in fans “disconnecting” from the fan community. Influenced by their self-identity structure, the choices of individual fans may vary significantly. This research proposes a social psychological model that not only offers a clearer explanation of fan identity psychology but also provides a theoretical reference for future research on dynamic changes in self-identity.